Emerging Market or Neighbourhood Country? A Case Study of Aura Light’s Market Expansion Strategy - Ria Triwastuti; Robert J. Poulter (TIJAB (The International Journal of Applied Business), 2018)
Aura Light, a Swedish lighting company, is currently in a transforming phase from a lighting products company into lighting solution provider. This change requires considerable new investments that resulted in the company’s cash operating cycle longer. However, there are two ambitions to pursue by the management of Aura Light in the next five years. Firstly, expanding market to India and Brazil by selling traditional products that potentially double its revenue in five years. Secondly, focusing on building the transformation and settling up solutions and LED market in Europe. Meanwhile, the long-term goal of Aura Light is to be a leader player of lighting solution and LED in Europe market. With current resources and financial condition, Aura Light can only choose one of those options instead of doing both at the same time. This study is aimed to answer Aura Lights dilemma by providing managerial recommendation based on international business theoretical frameworks.